Determination of the refractive index and wavelength‐dependent optical properties of few‐layer CrCl3 within the Fresnel formalism. (17th May 2021) - Kazim, Shafaq; Gunnella, Roberto; Zannotti, Marco; Giovannetti, Rita; Klimczuk, Tomasz; Ottaviano, Luca
Summary: Based on previous reports on the optical microscopy contrast of mechanically exfoliated few layer CrCl 3 transferred on 285 nm and 270 nm SiO 2 on Si(100), we focus on the experimental determination of an effective mean complex refractive index via a fitting analysis based on the Fresnel equations formalism. Accordingly, the layer and wavelength‐dependent absorbance and reflectance are calculated. Layer and wavelength‐dependent optical contrast curves are then evaluated demonstrating that the contrast is significantly high only around well‐defined wavelength bands. This is validated a posteriori, by experimental UV‐Vis absorbance data. The present study aims to show the way towards the most reliable determination of thickness of the 2D material flakes during exfoliation. Lay description: In this work, we focus on a fast and accurate determination of the number of layers and thickness of two‐dimensional (2D) CrCl 3 flakes. Like exfoliated graphite, MoS 2 or CrI 3, CrCl 3 has many interesting aspects for its physical properties, namely the magnetic ones. As Raman characterization cannot be used in the case of CrCl 3 for its insensitivity to the flake thickness, optical contrast, as obtained by an optical microscope equipped with a digital camera, can be suitable to determine the number of exfoliated layers in a single flake. Without any additional equipment, the contrast, as routinely optimized by using specific silicon oxide (270 and 285 nm thickness) on Si wafers, can be recorded and compared with Fresnel calculations for the interference. As a result, fitting of the experimental contrast as a function of average values of light wavelength, real and imaginary refraction index provides good sensitivity to the flake thickness and useful determination of the optical parameters. The latter ones are often different from their bulk properties. In addition to optical parameters, the determination is also independent from the light source characteristics. The present approach represents in this a way a precious, fast and cheap way to determine a crucial quantity of the 2D materials flakes production.